First-in-human dose escalation trial to evaluate the clinical safety and efficacy of an anti-MAGEA1 autologous TCR-transgenic T cell therapy in relapsed and refractory solid tumors - Ignacio I Wistuba; Mamta Kalra; Linus Backert; Martin Wermke; Edwin R Parra; Jason John Luke; Apostolia M Tsimberidou; Sebastian Bunk; Mohammad B Hossain; Andrea Mayer-Mokler; Arun Satelli; Norbert Hilf; et al. (Journal for ImmunoTherapy of Cancer)
Rationale of the trial Although the use of engineered T cells in cancer immunotherapy has greatly advanced the treatment of hematological malignancies, reaching meaningful clinical responses in the treatment of solid tumors is still challenging. We investigated the safety and tolerability of IMA202 in a first-in-human, dose escalation basket trial in human leucocyte antigen A*02:01 positive patients with melanoma-associated antigen A1 (MAGEA1)-positive advanced solid tumors.Trial design The 2+2 trial design was an algorithmic design based on a maximally acceptable dose-limiting toxicity (DLT) rate of 25% and the sample size was driven by the algorithmic design with a maximum of 16 patients. IMA202 consists of autologous genetically modified cytotoxic CD8+ T cells expressing a T cell receptor (TCR), which is specific for a nine amino acid peptide derived from MAGEA1. Eligible patients underwent leukapheresis, T cells were isolated, transduced with lentiviral vector carrying MAGEA1-specific TCR and following lymphodepletion (fludarabine/cyclophosphamide), infused with a median of 1.4×109 specific T cells (range, 0.086×109–2.57×109) followed by interleukin 2.Safety of IMA202 No DLT was observed. The most common grade 3–4 adverse events were cytopenias, that is, neutropenia (81.3%), lymphopenia (75.0%), anemia (50.0%), thrombocytopenia (50.0%) and leukopenia (25.0%). 13 patients experienced cytokine release syndrome, including one grade 3 event. Immune effector cell-associated neurotoxicity syndrome was observed in two patients and was grade 1 in both.Efficacy of IMA202 Of the 16 patients dosed, 11 (68.8%) patients had stable disease (SD) as their best overall response (Response Evaluation Criteria in Solid Tumors V.1.1). Five patients had initial tumor shrinkage in target lesions and one patient with SD experienced continued shrinkage in target lesions for 3 months in total but had to be classified as progressive disease due to progressive non-target lesions. IMA202 T cells were persistent in peripheral blood for several weeks to months and were also detectable in tumor tissue. Peak persistence was higher in patients who received higher doses.Conclusion In conclusion, IMA202 had a manageable safety profile, and it was associated with biological and potential clinical activity of MAGEA1-targeting genetically engineered TCR-T cells in a poor prognosis, multi-indication solid tumor cohort.Trial registration numbers NCT04639245, NCT05430555.